Analysis of Current COVID-19 Situations in Dental Practice among Karachi Population - Anas Sanaullah; Mahnoor KhawajaMSaleem; Abhishek Lal; Shayan Hemani; Naseer Ahmed; Muzamil M (ziauddin University, 2020)
Background: December 2019, marked the beginning of novel Coronavirus (COVID-19) from China (Wuhan), which hit the general population and healthcare systems, worldwide, as a pandemic. Karachi reported the first case of COVID-19 on February 26, 2020 in a student returning from Iran. Currently, World Health Organization has put forward specific guidelines for dental practitioners. The primary objective of the study was to determine the practices of dental practitioners in Karachi in following the standard guidelines set by the World Health Organization. Methods: In this, cross sectional questionnaire-based study, we have collected data from 111 dental practices through random sampling for analysis across Karachi, Pakistan. Structured questionnaire was designed comprising questions regarding knowledge, equipment, financial burden and procedures performed. Using SPSS version 25, descriptive analysis was executed on these variables. A multiple regression test was used to detect any relationship between them. Results: Majority (55.3%) of the dentists were found aware of the standard guidelines regarding dental practices and treatment of patients during COVID-19 outbreak but implementation in practice has been a major dilemma. Shortage of equipments as well as financial crisis was the main causative factors. Non-emergency procedures (5%) are being performed as well as inadequate protective measures are being adapted. Conclusion: According to the world standards, dental practices in Karachi should follow the standard guidelines put forward by world-renowned health organizations. Majority (p=0.44) of the dentists are aware of the standard guidelines, but lack of resources and financial instability are the primary factors affecting their dental practice.